(RS)‐Propranolol: enantioseparation by HPLC using newly synthesized (S)‐levofloxacin‐based reagent, absolute configuration of diastereomers and recovery of native enantiomers by detagging. (28th January 2016) - Alwera, Shiv; Bhushan, Ravi
Abstract: Diastereomers of ( RS )‐propranolol were synthesized using ( S )‐levofloxacin‐based new chiral derivatizing reagents (CDRs). Levofloxacin was chosen as the pure ( S )‐enantiomer for its high molar absorptivity ( ε o  ∼ 24000) and availability at a low price. Its ‐COOH group had N ‐hydroxysuccinimide and N ‐hydroxybenzotriazole, which acted as good leaving groups during nucleophilic substitution by the amino group of the racemic ( RS )‐propranolol; the CDRs were characterized by UV, IR, 1 H‐NMR, high resolution mass spectrometry (HRMS) and carbon, hydrogen, nitrogen, and sulphur fundamental elemental components analyser (CHNS). Diastereomers were separated quantitatively using open column chromatography; absolute configuration of the diastereomers was established and the reagent moiety was detagged under microwave‐assisted acidic conditions. ( S )‐ and ( R )‐propranolol as pure enantiomers and ( S )‐levofloxacin were separated, isolated and characterized. Optimized lowest‐energy structures of the diastereomers were developed using Gaussian 09 Rev. A.02 program and hybrid density functional B3LYP with 6‐31G* basis set (based on density functional theory) for explanation of elution order and configuration. In addition, RP HPLC conditions for separation of diastereomers were optimized with respect to pH, concentration of buffer, flow rate of mobile phase and nature of organic modifier. HPLC separation method was validated as per International Conference on Harmonization guidelines. With the systematic application of various analytical techniques, absolute configuration of the diastereomers (and the native enantiomers) of ( R S )‐propranolol was established. Copyright © 2016 John Wiley & Sons, Ltd.